Clinical Application of Xenon in Subanesthetic Concentrations (Review) - M. E. Politov; S. V. Podprugina; E. N. Zolotova; P. V. Nogtev; Yu. S. Agakina; S. G. Zhukova; A. G. Yavorovsky (Общая реаниматология)
Xenon is considered to be the safest general anesthetic agent with organ-protective properties. In subanesthetic doses, it is recognized as a promising therapeutic agent in various medical fields.The aim of this review was to systematically summarize scientific data on the potential therapeutic use of xenon for organ system protection outside the context of anesthetic support during surgery and perioperative analgesia.Publications were searched in the databases PubMed, Google Scholar, Cochrane Library, and eLIBRARY.RU from August to September 2024. A total of 33 publications on the clinical use of inhaled xenon for therapeutic purposes from 2002 to 2023 were selected, including 12 randomized controlled trials (RCTs), 8 prospective controlled studies, 2 prospective comparative studies, 6 prospective uncontrolled studies, and 2 clinical observations. An additional 32 publications were used to discuss various aspects related to the topic of the review.Conclusion. The literature review showed that inhaled xenon at subanesthetic doses has potential neuroprotective, cardioprotective, and therapeutic effects for the treatment of addictive and neurotic disorders, as well as oncologic and pulmonary conditions. Despite some promising results, the number of RCTs remains limited, and the existing studies have methodological limitations, small sample sizes, and a high risk of systematic error. Definitive conclusions regarding the clinical eﬃcacy and safety of inhaled xenon require further large-scale randomized trials.